Alekszej Csheidze, egy Magyarországon harcolt szovjet katona feljegyzései - Nagy, László (Studia Litteraria, 2020)
There are very few published memoirs of Soviet soldiers who fought in the Second World War, despite the fact that the narratives of the ones who survived this loaded historical period may significantly shape our understanding of it. The deeds of Soviet soldiers fighting in Hungary varies greatly, from genocide to rescue, which topic is touched upon by the paper. The article provides the translation technical analysis of the notes of the Georgian Soviet soldier, Alexei Alexandrovich Chkheidze, who fought in Hungary and met a tragic fate. It gives prominence to the fact that the literary translator often has to do the work of a technical translator: they must thoroughly research the contemporary military jargon and clothing, as well as the altered naming of various locations.